Kata Satuan Bahasa Korea dalam bidang Kuliner - Lintang, Ridwan Giffary; Kesuma, Tri Mastoyo Jati (DBSMB, Vocational College of Universitas Gadjah Mada, 2023)
Measure word is a group of words functions as a noun counter and complementing a numeral. Each language has a different set and types of measure words. Korean has a lot of measure words and it is used based on the semantic feature of the counted noun. This paper examines types of Korean measure words in a culinary-related text. Data were collected from recipes written in Korean. Then, Data were classified and analyzed to see the similarities and differences between those measure words. Our results showed that there are four types of Korean measure words. First, measure words that are standard measurement units (e.g geuraem 'gram' and litheo 'liter'). Second, measure words that are Korean traditional measurement units like geun. Third, measure words that came from measuring tools like byeong 'bottle' and keunsul 'spoon' and the last, measure words that are classifiers. In a phrasal structure, measure words placed after the numeral, and the noun is mainly placed before the numeral but it also can be placed after the measure words by adding a genitive particle -eui between the measure word and noun. Commonly-used measure words and classifiers that have one-to-one equivalent word in Indonesian will be easier to learn by learners from Indonesian background.